1994
DOI: 10.1017/s0021932000021635
|View full text |Cite
|
Sign up to set email alerts
|

Age of mother at last birth in two historical populations

Abstract: This study uses sets of historical family reconstitutions from all of Quebec and from four villages of the Haut-Jura, France-first marriages of 2226 and 994 women, respectively-to investigate the physiological and social factors affecting age of mother at last birth before and during fertility transition. Age remained high throughout the period covered in Quebec, under 'natural' conditions, but showed a steady decline in the French material which extends to late 19th century generations practising family limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Figure 3 includes plots of the cumulative distribution of ages at last delivery for three natural fertility populations: 2,462 women who were born 1845–1849 and lived to the age of 50 or later from the Utah Population Database (UPDB; Bean et al, 1990), 2,678 women born before 1715 in Quebec (Desjardins et al, 1994), and 1,578 women born before 1750 in four French villages of the Haut-Jura (Desjardins et al, 1994). As Figure 3 indicates, 5–17% of women may have had their last delivery by the age of 35, whereas another 10% do not do so until after 45.…”
Section: Fertility Decline Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 includes plots of the cumulative distribution of ages at last delivery for three natural fertility populations: 2,462 women who were born 1845–1849 and lived to the age of 50 or later from the Utah Population Database (UPDB; Bean et al, 1990), 2,678 women born before 1715 in Quebec (Desjardins et al, 1994), and 1,578 women born before 1750 in four French villages of the Haut-Jura (Desjardins et al, 1994). As Figure 3 indicates, 5–17% of women may have had their last delivery by the age of 35, whereas another 10% do not do so until after 45.…”
Section: Fertility Decline Comparisonsmentioning
confidence: 99%
“…Age at last parturition data come from three natural fertility populations (Utah data from UPDB, 2006; French data from Desjardins et al, 1994; Quebecois data from Müller et al, 2002). Age at menopause from four populations (Minnesota data from Treolar, 1981; Australia data from Do et al, 1998; Puebla data from Sievert and Hautaniemi, 2003; Norway data from Jacobsen et al, 2003).…”
Section: Figmentioning
confidence: 99%
“…All the ancestors of every individual who married before 1800 were traced back to the founders of the population. Previous studies have shown that the population of that period lived under 'natural fertility' conditions, as defined by Henry (Henry, 1972) as it was free of deliberate fertility control (Charbonneau, 1993;Desjardins et al, 1994;Desjardins et al, 1991).…”
Section: Data and Selection Of Casesmentioning
confidence: 99%
“…The mean age at last birth is remarkably invariant in natural fertility populations. With few exceptions, the means fall in the 39 -41year range (Bongaarts and Potter, 1983;Desjardins et al, 1994). These results suggest that the timing of the onset of natural sterility varies little among populations, except in cases where sexual infectious diseases are widespread.…”
Section: Discussionmentioning
confidence: 86%